Association between vitamin D deficiency and major depression in patients with chronic kidney disease: a cohort study - Chen, I-Wen; Wang, Wei-Ting; Lai, Yi-Chen; Chang, Ying-Jen; Lin, Yao-Tsung; Hung, Kuo-Chuan (Frontiers in Nutrition, 2025)
BackgroundPatients with chronic kidney disease (CKD) have an elevated risk of both vitamin D deficiency (VDD) and depression. However, the relationship between VDD and the risk of depression in this population remains unclear.MethodsUsing the TriNetX network database (2010–2019), we conducted a propensity score-matched cohort study of CKD patients aged ≥50 years. Patients were categorized into VDD (≤20 ng/mL) and control (≥30 ng/mL) groups based on measurements within 3 months of CKD diagnosis. The primary outcome was the incidence of major depression within 1 year of follow-up.ResultsAmong 17,955 matched pairs, VDD was associated with increased depression risk at 1 year (hazard ratio [HR]: 1.929; 95% confidence interval [CI]: 1.52–2.448; p < 0.0001). This association persisted through 3 years of follow-up. The relationship remained consistent across CKD stages, with similar risks in early (HR:1.977; 95% CI: 1.382–2.829) and CKD stage 3–5 (HR:1.981; 95% CI: 1.533–2.559). Males with VDD showed higher depression risk (HR: 2.264; 95% CI: 1.498–3.421) compared to females (HR:1.761; 95% CI: 1.307–2.374). Even vitamin D insufficiency (20–30 ng/mL) increased depression risk compared to normal levels (HR:1.667; 95% CI: 1.318–2.11). In patients with VDD, cerebrovascular disease, malnutrition, and ischemic heart disease are risk factors for depression.ConclusionVDD is independently associated with increased depression risk in patients with CKD, particularly in males. These findings suggest that maintaining adequate vitamin D levels might be important for mental health in patients with CKD, although randomized trials are needed to confirm whether supplementation can prevent depression in this population.